The study of anthropometric points that change based on the movement of parachutists in the airspace - A. Zh. Abekova; A. Zh. Talgatbekova; N. B. Rahmetova (Алматы технологиялық университетінің хабаршысы, 2023)
When designing parachutists' clothing in the airspace, it is necessary to take into account the influence of dangerous and harmful factors in relation to them, including external environmental factors in which the parachutist is located, functional positions, movements performed by parachutists are established and analyzed, as well as consumer preferences are studied in detail. The process of designing a suit for skydiving in airspace includes the following important stages: the relationship of clothing and anthropometric points in accordance with the requirements of ergonomics. It takes into account the choice of a package of materials based on comparable characteristics of clothing in the process of protecting the human body, the development of the design of the projected product based on a mathematical model, the reduction of the process of long-term study of the structure. And at the design stage, it allows you to get products with a high level of ergonomics. The proposed information and logical scheme for designing an ergonomic suit for skydiving allows you to determine the type, sequence and relationship of work at each stage of the design. In the course of the study, polynomial dependences of changes in the dynamic effects of dimensional features of parachutists' figures on angular biomechanical parameters of movements in the main links were revealed. Special clothing that determines the compliance of parachutists in the airspace with the conditions of the study of anthropometric points that change based on movement is determined by functional and ergonomic features. At the same time, the variability of the type of the initial model designs of workwear is justified in accordance with the variety of design conditions for movement in airspace.